From Catholic to Protestant : religion and the people in Tudor England - Rosman, Doreen M. (Introductions to history., 1996)
This work, aimed at students unfamiliar with religious ideas and terminology, attempts to convey the centrality of religion to people's lives in early modern England, and to understand why people were prepared to die and kill for their faith.